Factors Affecting Modern Costing Methods in Jordanian Industrial Companies - Chakroun, Raida; Saadeddin, Omar Jamil (Technium Social Sciences Journal, 2025)
The study in Jordanian industrial companies will identify factors affecting modern costing methods using SPSS and a multiple regression model to test hypotheses. The study includes 577 Jordanian industrial companies with a total of 2,714 employees. The sample size consists of 271 questionnaires, representing 10% of the total number of employees in these companies. The study found that factors such as company size, governance, and the quality of internal audits have an impact on modern costing methods like target costs, environmental costs, and activity-based costs. The study recommended further research to better understand how manufacturing environment variables influence the adoption of modern costing in Jordanian companies, as it is a strategic management accounting tool for companies in developing economies like Jordan.